PORROCAECUM DASYATUM N. SP. (NEMATODA : HETEROCHEILIDAE) FROM THE STOMACH OF RAY FISH, DASYATIS UARNAK (FORSKAL) FROM VISAKHAPATNAM - RAJYALAKSHMI, I.; VIJAYALAKSHMI, C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
The description of a new species of nematode ot the family Heterocheilidae Railliet et Henry, 1915, recovered from stomach of Dasyatis uarnak from Visakhapatnam is described. The new species is characterized by body measurements, length of oesophagus and intestinal caecum, number and arrangement of caudal papillae, position of length of spicules, position of vulva and structure of tail end. Thus it could be considered as a new species, Porrocaecum dasyatum.